DETECTION OF BETA-DEFENSINS AND NOS IN HEALTHY AND PATHOLOGICAL NASAL MUCOSA - Pacova, Hana; Kucera, Tomas; Astl, Jaromir; Martinek, Jindrich (Biomedical papers, 2004)
...
Keywords: Beta-defensin/Nitric oxide synthase/Apoptosis/Cell proliferation/Nasal polyposis